TRANSFORMATION OF LANGUAGE TRAINING IN HIGHER TECHNICAL EDUCATION INSTITUTIONS - Pryshupa, Yuliia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article analyses the language training implemented in the process of teaching foreign languages in higher technical education institutions. The study includes the challenges of the present, the requirements of globalization, and the digitization of education. The transformation of the role of language training and key aspects in this context, including technological orientation and communicative potential, are considered. A comparative analysis of the acquired experience and the effectiveness of implementing prospective directions for the development and improvement of language training for students in higher technical education is also provided. This includes the use of innovative methods for learning foreign languages based on the application of information and educational technologies and the quality of foreign language teaching. Special attention is given to the essence of language training in higher technical education institutions, which involves professionally oriented communication competence as a crucial tool for successful adaptation to new educational environments. The author of the article explores the benefits of integrating an information and educational environment into the language training process and proves the importance of systematically assessing the current situation in language training to establish continuity in development stages and accumulate experience. The purpose of the study is the theoretical substantiation and empirical investigation of the current state of language training in higher technical education institutions. Objectives of the study are focused on the scientific substantiation of the concepts of “transformation”, “language training in higher technical education institutions”; and the identification of qualitative changes in language training and contradictions that hinder the achievement of the desired results and high quality of foreign language teaching. The results of the study prove that the educational and information environment is a combination of the latest information technologies and modern pedagogical developments, which should lead to the maximum effect of a sufficient educational process. Various roles of the educational and information environment in the educational process are considered. Where the specified environment can be both a means of supporting the educational process and a means of implementing blended learning. In our study, the educational and informational environment is considered in the paradigm of the distance learning organization. The classification of the levels of the information and educational space and the requirements for distance learning is revealed. The research proposes and justifies the choice of Internet technologies to create a new level of education and information environment. Research also proved the establishment of contact between all participants of the educational process; sample settings are necessary when the students’ load of educational material is determined. In the course of questionnaires and surveys of participants in the educational and pedagogical process of technical universities, the peculiarities of the organization of professional training of future specialists in the conditions of distance learning, their influence on the success of language personality formation, and motivation to study were established. Conclusions. Summarizing the research results on language transformations in higher technical education institutions, the author substantiates the importance of conducting systematic assessment of the current language training situation. It is noted that transformative processes in language training open up opportunities to reveal uniqueness aimed at combining the information and educational environment and intra-subject connections in higher technical education institutions based on common contemporary ideas and concepts. The retrospective analysis allowed tracing the evolution of language training in higher technical education institutions, represented as a multi-stage process containing transformations and innovations in the search for more effective approaches. The assessment of the current situation at the university also identified problems and contradictions hindering the achievement of desired results and high-quality foreign language teaching. These positive trends have led to the formation of the university’s information and educational environment, a wide range of methodological developments, and mechanisms to improve the effectiveness of language training. The obtained results indicate the achievement of the research objective